Introduction
Phase 1: System of Linear Equations
Gauss Elimination
Gauss Jordan
LU Decomposition
Doolittle's Method
Crout's Method
Cholesky's Method
Gauss Seidel
Jacobi-Iteration
Phase 2: Root Finding
Bisection
False-Position
Fixed Point
Original Newton-Raphson
Modified Newton-Raphson
Modification 1
Modification 2
Secant Method
The project "Equator" stands as a robust mathematical toolkit, built upon the foundation of Python and PyQt, enriched by the inclusion of powerful libraries such as NumPy, SymPy, and Matplotlib. Its overarching goal is to deliver efficient numerical solutions to a diverse array of mathematical challenges, with a specific emphasis on problems related to linear algebra and root finding. The project is divided into two phases, each of which is further subdivided into several modules. The first phase is dedicated to the solution of systems of linear equations, while the second phase is dedicated to the solution of root finding problems. The project is designed to be user-friendly, with a simple and intuitive graphical user interface (GUI) that allows the user to easily interact with the program and obtain the desired results.
Phase 1: System of Linear Equations
$$
\begin{align*}
&\text{Forward Elimination:} \\
&\begin{bmatrix}
\begin{array}{ccc|c}
a_{11} & a_{12} & a_{13} & b_1 \\
a_{21} & a_{22} & a_{23} & b_2 \\
a_{31} & a_{32} & a_{33} & b_3 \\
\end{array}
\end{bmatrix}
\sim
\begin{bmatrix}
\begin{array}{ccc|c}
a_{11} & a_{12} & a_{13} & b_1 \\
0 & a_{22}' & a_{23}' & b_2' \\
0 & 0 & a_{33}'' & b_3'' \\
\end{array}
\end{bmatrix}\\
&\text{Backward Substitution:} \\
&\begin{aligned}
x_3 &= \frac{b_3''}{a_{33}''} \\
x_2 &= \frac{b_2' - a_{23}'x_3}{a_{22}'} \\
x_1 &= \frac{b_1 - a_{12}x_2 - a_{13}x_3}{a_{11}} \\
\end{aligned}
\end{align*}
$$
$$
\begin{aligned}
2x_1 + 3x_2 - 2x_3 &= 1 \\
4x_1 + 4x_2 - 3x_3 &= 5 \\
2x_1 - x_2 + 2x_3 &= 3 \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
Step 8:
Step 9:
Step 10:
$$
\begin{align*}
&\text{Forward and Backward Elimination:} \\
&\begin{bmatrix}
\begin{array}{ccc|c}
a_{11} & a_{12} & a_{13} & b_1 \\
a_{21} & a_{22} & a_{23} & b_2 \\
a_{31} & a_{32} & a_{33} & b_3 \\
\end{array}
\end{bmatrix}
\sim
\begin{bmatrix}
\begin{array}{ccc|c}
a_{11} & 0 & 0 & b_1'' \\
0 & a_{22}' & 0 & b_2'' \\
0 & 0 & a_{33}'' & b_3'' \\
\end{array}
\end{bmatrix} \ \\
&\text{Normalization:} \\
&\begin{bmatrix}
\begin{array}{ccc|c}
1 & 0 & 0 & b_1''/a_{11} \\
0 & 1 & 0 & b_2''/a_{22}' \\
0 & 0 & 1 & b_3''/a_{33}'' \\
\end{array}
\end{bmatrix}
\begin{aligned}
x_1 = \frac{b_1''}{a_{11}},\quad
x_2 = \frac{b_2''}{a_{22}'} ,\quad
x_3 = \frac{b_3''}{a_{33}''} \\
\end{aligned}
\end{align*}
$$
$$
\begin{aligned}
2x_1 + 3x_2 - 2x_3 &= 1 \\
4x_1 + 4x_2 - 3x_3 &= 5 \\
2x_1 - x_2 + 2x_3 &= 3 \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
Step 8:
Step 9:
$$
A = LU \text{ where } L \text{ is a lower triangular matrix and } U \text{ is an upper triangular matrix}\\
$$
$$
LUx = b \implies Ux = y \text{ and } Ly = b
$$
$$
\begin{bmatrix}
a_{11} & a_{12} & a_{13} \\
a_{21} & a_{22} & a_{23} \\
a_{31} & a_{32} & a_{33} \\
\end{bmatrix}
=\begin{bmatrix}
1 & 0 & 0 \\
l_{21} & 1 & 0 \\
l_{31} & l_{32} & 1 \\
\end{bmatrix}
\begin{bmatrix}
u_{11} & u_{12} & u_{13} \\
0 & a_{22} & u_{23} \\
0 & 0 & u_{33} \\
\end{bmatrix}
$$
$$
\begin{aligned}
3x_1 + 2x_2 - x_3 &= 1 \\
2x_1 + 3x_2 + 2x_3 &= 2 \\
5x_1 - x_2 + 4x_3 &= 3 \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
$$
\begin{bmatrix}
a_{11} & a_{12} & a_{13} \\
a_{21} & a_{22} & a_{23} \\
a_{31} & a_{32} & a_{33} \\
\end{bmatrix}
=\begin{bmatrix}
l_{11} & 0 & 0 \\
l_{21} & l_{22} & 0 \\
l_{31} & l_{32} & l_{33} \\
\end{bmatrix}
\begin{bmatrix}
1 & u_{12} & u_{13} \\
0 & 1 & u_{23} \\
0 & 0 & 1 \\
\end{bmatrix}
$$
$$
\begin{aligned}
3x_1 + 2x_2 - x_3 &= 1 \\
2x_1 + 3x_2 + 2x_3 &= 2 \\
5x_1 - x_2 + 4x_3 &= 3 \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
$$
A = A^T \implies A = LL^T \\
$$
$$
\begin{bmatrix}
a_{11} & a_{12} & a_{13} \\
a_{21} & a_{22} & a_{23} \\
a_{31} & a_{32} & a_{33} \\
\end{bmatrix}
=\begin{bmatrix}
l_{11} & 0 & 0 \\
l_{21} & l_{22} & 0 \\
l_{31} & l_{32} & l_{33} \\
\end{bmatrix}
\begin{bmatrix}
l_{11} & l_{21} & l_{31} \\
0 & l_{22} & l_{32} \\
0 & 0 & l_{33} \\
\end{bmatrix}
$$
$$
\begin{aligned}
5x_1 + 2x_2 + x_3 &= 1 \\
2x_1 + 6x_2 + 2x_3 &= 2 \\
3x_1 + 2x_2 + 7x_3 &= 3 \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
$$
\begin{aligned}
x_1^{(k+1)} &= \frac{b_1 - a_{12}x_2^{(k)} - a_{13}x_3^{(k)}}{a_{11}} \\
x_2^{(k+1)} &= \frac{b_2 - a_{21}x_1^{(k+1)} - a_{23}x_3^{(k)}}{a_{22}} \\
x_3^{(k+1)} &= \frac{b_3 - a_{31}x_1^{(k+1)} - a_{32}x_2^{(k+1)}}{a_{33}} \\
\end{aligned}
$$
$$
\begin{aligned}
&4x_1 + 2x_2 + x_3 &= 11 \\
&-1x_1 + 2x_2 &= 3 \\
&2x_1 + x_2 + 4x_3 &= 16 \\
&x_0 = (1, 1, 1) \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
$$
\begin{aligned}
x_1^{(k+1)} &= \frac{b_1 - a_{12}x_2^{(k)} - a_{13}x_3^{(k)}}{a_{11}} \\
x_2^{(k+1)} &= \frac{b_2 - a_{21}x_1^{(k)} - a_{23}x_3^{(k)}}{a_{22}} \\
x_3^{(k+1)} &= \frac{b_3 - a_{31}x_1^{(k)} - a_{32}x_2^{(k)}}{a_{33}} \\
\end{aligned}
$$
$$
\begin{aligned}
&4x_1 + 2x_2 + x_3 &= 11 \\
&-1x_1 + 2x_2 &= 3 \\
&2x_1 + x_2 + 4x_3 &= 16 \\
&x_0 = (1, 1, 1) \\
\end{aligned}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
Step 8:
Step 9:
Step 10:
Step 11:
$$
x_{r} = \frac{x_{l} + x_{u}}{2}
\begin{cases}
x_{u} = x_{r}, & \text{if } f(x_{l}) \cdot f(x_{r}) < 0 \\
x_{l} = x_{r}, & \text{if } f(x_{l}) \cdot f(x_{r}) > 0 \\
\text{root} = x_{\text{r}}, & \text{if } f(x_{l}) \cdot f(x_{r}) = 0
\end{cases}
$$
$$
f(x) = -12 - 21x + 18x^2 - 2.75x^3
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
Step 8:
Step 9:
$$
x_{r} = \frac{x_{l} \cdot f(x_{u}) - x_{u} \cdot f(x_{l})}{f(x_{u}) - f(x_{l})}
\begin{cases}
x_{u} = x_{r}, & \text{if } f(x_{l}) \cdot f(x_{r}) < 0 \\
x_{l} = x_{r}, & \text{if } f(x_{l}) \cdot f(x_{r}) > 0 \\
\text{root} = x_{\text{r}}, & \text{if } f(x_{l}) \cdot f(x_{r}) = 0
\end{cases}
$$
$$
f(x) = -12 - 21x + 18x^2 - 2.75x^3
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
$$
x_{i+1} = g(x_{i})
$$
$$
f(x) = \sin{\sqrt{x}} - x, \quad g(x) = \sin{\sqrt{x}}
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
Step 6:
Step 7:
Step 8:
Step 9:
4. Original Newton-Raphson
$$
x_{i+1} = x_i - \frac{f(x_i)}{f'(x_i)}
$$
$$
f(x) = -0.9x^2 + 1.7x + 2.5
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
Step 5:
5. Modified Newton-Raphson
$$
x_{i+1} = x_i - m \cdot \frac{f(x_i)}{f'(x_i)}
$$
$$
f(x) = x^3 - 5x^2 + 7x - 3
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
$$
x_{i+1} = x_i - \frac{f(x_i) \cdot f'(x_i)}{(f'(x_i))^2 - f(x_i) \cdot f''(x_i)}
$$
$$
f(x) = x^3 - 5x^2 + 7x - 3
$$
Steps
Step 1:
Step 2:
Step 3:
Step 4:
$$
x_{i+1} = x_i - \frac{f(x_i) \cdot (x_i - x_{i-1})}{f(x_i) - f(x_{i-1})}
$$
$$
f(x) = x^3 - 6x^2 + 11x - 6.1
$$
Steps
Step 1:
Step 2:
Step 3: